Pengaruh Self Control dan Financial Attitude terhadap Financial Management Behavior pengguna Layanan Buy Now Pay Later - Namira Maulida Eka Putri; Sonja Andarini (Universitas Jember, 2022)
This study aims to analyze the significant influence between self control and financial attitude on the financial management behavior of users of buy now pay later services. This research uses quantitative research with a descriptive approach. The population in this study are residents of the city of Surabaya who use Shopee Paylater. The number of samples in this study were 115 respondents. In this study using the Non-Probability Sampling technique with purposive sampling technique. The analysis technique used is multiple linear regression analysis. The results of this study indicate that the self-control variable partially has a significant effect on the financial management behavior of buy now pay later service users, the financial attitude variable partially has a significant effect on the financial management behavior of buy now pay later service users, self control and financial attitude variables simultaneously have an effect. significant to the financial management behavior of users of the buy now pay later service. Keywords: self control, financial attitude, financial management behavior, buy now pay later